Subconjunctival hemorrhage and modern treatment approaches - I.V. Vorobyeva; M.A. Frolov; A.M. Frolov; D.A. Trofimova; S. Shallah (РМЖ "Клиническая офтальмология")
I.V. Vorobyeva, M.A. Frolov, A.M. Frolov, D.A. Trofimova, S. Shallah RUDN University, Moscow, Russian Federation Every ophthalmologist sees patients with subconjunctival hemorrhage (SCH). SCH can mask serious diseases that threaten not only vision but also life. The authors analyze SCH in my-ocardial infarction, coronary artery stenting, COVID-19, childbirth, and ocular surgery. It has been shown that free radicals, oxidative stress, and reactive oxygen species increase the permea-bility of conjunctival capillaries and cause the vessels to become "fragile" which are the basis for SCH. Oxidative stress and free radicals are involved in corneal and lens damage and are pathogenic factors in glaucoma and diabetic retinopathy. A modern approach to the treatment of SCH is the administration of methylethylpyridinol (eye drops), which shortens the time of hem-orrhage absorption. Methylethylpyridinol has a positive effect on many eye diseases, such as glaucoma, diabetic retinopathy, and neuropathy. Further studies on the efficacy of meth-ylethylpyridinol in SCH and other ocular diseases seem relevant. Keywords: subconjunctival hemorrhage (SCH), myocardial infarction, stroke, oxidative stress, methylethylpyridinol. For citation: Vorobyeva I.V., Frolov M.A., Frolov A.M., Trofimova D.A., Shallah S. Subconjunctival hemorrhage and modern treatment approaches. Russian Journal of Clinical Ophthalmology. 2024;24(3):138–143 (in Russ.). DOI: 10.32364/2311-7729-2024-24-3-8.